PsrA controls the synthesis of the Pseudomonas aeruginosa quinolone signal via repression of the FadE homolog, PA0506 - Wells, Greg (PLoS One, 2017)
Pseudomonas aeruginosa is a ubiquitous, Gram-negative opportunistic pathogen that can cause disease in various sites within the human body. This bacterium is a major source of nosocomial infections that are often difficult to treat due to high intrinsic antibiotic resistance and coordinated virulence factor production. P. aeruginosa utilizes three cell-to-cell signaling systems to regulate numerous genes in response to cell density. One of these systems utilizes the small molecule 2-heptyl-3-hydroxy-4-quinolone (Pseudomonas quinolone signal [PQS]) as a signal that acts as a co-inducer for the transcriptional regulator PqsR. Quinolone signaling is required for virulence in multiple infection models, and PQS is produced during human infections, making this system an attractive target for potential drug development. In this study we have examined the role of a TetR-type transcriptional regulator, PsrA, in the regulation of PQS production by P. aeruginosa. Previous studies showed that PsrA regulates genes of the fatty acid β-oxidation pathway, including PA0506, which encodes a FadE homolog. In this report, we show that deletion of psrA resulted in a large decrease in PQS production and that co-deletion of PA0506 allowed PQS production to be restored to a wild type level. We also found that PQS production could be restored to the psrA mutant by the addition of oleic or octanoic acid. Taken together, our data suggest that psrA positively affects PQS production by repressing the transcription of PA0506, which leads to a decrease in the conversion of acyl-CoA compounds to enoyl-CoA compounds, thereby allowing some octanoyl-CoA to escape the ß-oxidation pathway and serve as a PQS precursor.